The Impact of Husband's Support and Economic Status on the Fulfillment of Pregnant Women's Nutrition in the Air Itam Health Center Work Area - Amelia, Fitra; Hajar, Siti (Journal of Midwifery and Nursing, 2025)
Balanced nutrition is a daily food arrangement that contains nutrients in types and amounts that meet the body's needs by considering the principles of diversity or variety of foods, physical activity, cleanliness, and ideal body weight. Objective: To determine the relationship between the husband's support and economic status on the fulfillment of pregnant women's nutrition in preventing stunting in the Air Itam Health Center work area in 2024. Method: This study uses a quantitative analytical approach with a cross-sectional design and a Chi-square test, with the analysis results in univariate and bivariate analysis. Results of the study: This proves a relationship between husband's support (p = 0.002) and economic status (p = 0.001) with the fulfillment of nutrition in pregnant women in the Air Itam Health Center work area in 2024. Conclusion: A relationship exists between husband's support and nutrition fulfillment in pregnant women in the Air Itam Health Center work area in 2024. There is a relationship between economic status and nutrition fulfillment in pregnant women in the Air Itam Health Center work area in 2024Balanced nutrition is a daily food arrangement that contains nutrients in types and amounts that meet the body's needs by considering the principles of diversity or variety of foods, physical activity, cleanliness, and ideal body weight. Objective: To determine the relationship between the husband's support and economic status on the fulfillment of pregnant women's nutrition in preventing stunting in the Air Itam Health Center work area in 2024. Method: This study uses a quantitative analytical approach with a cross-sectional design and a Chi-square test, with the analysis results in univariate and bivariate analysis. Results of the study: This proves a relationship between husband's support (p = 0.002) and economic status (p = 0.001) with the fulfillment of nutrition in pregnant women in the Air Itam Health Center work area in 2024. Conclusion: A relationship exists between husband's support and nutrition fulfillment in pregnant women in the Air Itam Health Center work area in 2024. There is a relationship between economic status and nutrition fulfillment in pregnant women in the Air Itam Health Center work area in 2024